The Hel Peninsula as a water sports center: Tourist preferences and expectations - Busko, Paulina; Majdak, Piotr (Turystyka – to znaczy co? Uroboros czy Feniks, 2025)
The considerations presented in the article focus on issues related to the preferences and expectations of tourists practicing water sports on the Hel Peninsula in relation to various groups of tourism assets such as natural conditions, infrastructure or availability of services. The aim of the work is to identify the key factors influencing the attractiveness of the region, taking into account the perspectives of those actively using its water potential. The first part of the article presents a framework description of the assets of the Hel Peninsula, important from the point of view of practicing water sports. Then, the results of a survey conducted among tourists actively using the offer of water sports there are presented. The analyses conducted aim to identify the key factors influencing the choice of this region as a sports and recreation destination, the types of preferred activities, expectations regarding infrastructure, the quality of services and the natural conditions conducive to practicing water sports. The final part presents a summary of the research results, indicating key conclusions regarding perceptions of the tourism assets of the Hel Peninsula by those practicing water sports. On this basis, recommendations were formulated regarding future action that could contribute to the further development of the tourism offer.